Hydroflux Synthesis and Characterization of the Non-Centrosymmetric Oxomanganate(V) KSrMnO4 - Albrecht, Ralf; Doert, Thomas; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2020)
Bluish-green crystals of the oxomanganate(V) KSrMnO4 were synthesized under hydroflux conditions with KOH at about 200 °C starting from KMnO4 and Sr(NO3)2. The product formation depends on the hydroxide concentration and the strontium-manganese ratio of the starting materials. By changing these parameters, also other reaction products, such as α-SrMnO3 and Sr5[MnO4]3OH, are obtained. KSrMnO4 crystallizes in the non-centrosymmetric orthorhombic space group P212121 with a = 743.26(7) pm, b = 575.72(6) pm and c = 987.2(1) pm. The crystal structure consists of isolated [MnO4]3– tetrahedra surrounded by Sr2+ and K+ cations. The group-subgroup relation to KBaMnO4 and to the aristotype α-K2SO4 are discussed. UV/Vis spectra and magnetic data agree with the oxidation state +V of manganese. KSrMnO4 is paramagnetic, but orders as an antiferromagnet below 4.6(1) K. Thermal analysis of KSrMnO4 revealed the decomposition at about 950 °C to α-SrMnO3.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Crystal structure; Hydroflux synthesis; Magnetic properties; Manganese; Spectroscopy